The Influence of Emotional Engagement on Sentence Comprehension Process in a Second Language - Fatimah, Ade Fitria (Sekolah Tinggi Agama Islam Kuningan, 2025)
This study aims to uncover the influence of emotional engagement on sentence comprehension processes in second language learning. Qualitative methods were applied with observation, in-depth interviews, and thematic analysis of actively engaged participants. Results show that positive emotions, such as enthusiasm and curiosity, play an important role in facilitating cognitive processing and encouraging collaborative participation. Negative emotions, on the other hand, can be a barrier, requiring appropriate emotion management strategies. The practical implication is the importance of affective learning design to improve motivation and sentence comprehension performance.